Social Internet of Things their Trustworthiness Node Rank and Embedding’s Management (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
The goal is to reduce service delivery times by identifying and selecting suitable online devices to do the required computational operations. Future embedded device networks may be significantly altered by the SIoT idea, which will allow for interoperability between previously isolated devices. The potential gains from implementing such systems might be amplified by double if this opens the way for cutting-edge data fusion techniques. Even while first results from IoT research have been encouraging, there is still a lot of room for development in the industry. In this study, we focus on one such use case: community detection in emergency response. Similarity measures find similar data points while studying graph components. The graph represents the information or data that is the subject of the analysis.